Manfaat Metode Bercerita Terhadap Kemampuan Sosial Emosional Anak Usia Dini - Siswanti, Dian Novita; Daud, Muh. (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to determine the benefits of the storytelling method on the social emotional abilities of young children. This research uses a library research method using data sources in the form of 9 scientific articles related to storytelling methods, social emotional abilities, early childhood. The data obtained was analyzed using content analysis with stages of problem identification, literature collection, literature analysis, interpretation and drawing up conclusions regarding the effectiveness of the storytelling method in improving the social emotional abilities of young children. The research results show that the storytelling method has proven to be effective in developing social emotional skills in early childhood. Through stories, children learn to recognize and manage their emotions, understand other people's feelings, and behave in accordance with applicable social norms. The application of this method in learning at PAUD can help improve social emotional skills which are important for preparing children to enter the next level of education. This research concludes that there is a positive impact of the storytelling method on improving socioemotional abilities in early childhood. The implications of this research can be useful for parents and PAUD teachers in using storytelling methods to stimulate socio-emotional abilities in early childhood